Geometric Flows and the Geometry of Space-time (Tutorials, Schools, and Workshops in the Mathematical Sciences ,, 2018)
This book consists of two lecture notes on geometric flow equations (O. Schnürer) and Lorentzian geometry - holonomy, spinors and Cauchy Problems (H. Baum and T. Leistner) written by leading experts in these fields. It grew out of the summer school "Geometric flows and the geometry of space-time" held in Hamburg (2016) and provides an excellent introduction for students of mathematics and theoretical physics to important themes of current research in global analysis, differential geometry and mathematical physics.